ANALISIS OPTIMASI KEUNTUNGAN PENJUALAN UMKM BERBASIS QM FOR WINDOWS MENGGUNAKAN METODE SIMPLEKS - Amelia Rumaropen; Heru Sutejo, Michella Kabuare, Cazanova Porat, Agnes Wanggai, Tiasa Sitohang (Jurnal Ekonomi dan Bisnis, 2026)
UMKM Basyira Kukis is a micro, small, and medium enterprise (MSME) engaged in the production and sale of cookies, which often faces challenges in determining production quantities due to limited resources such as raw materials, production time, and workforce. This study aims to determine the optimal production combination to maximize profit using Linear Programming method. Data collection was carried out through observation, interviews, and literature study, including information on raw material usage, production costs, selling prices, production capacity, and working hours. A linear programming model was formed consisting of an objective function to maximize profit and several constraint functions based on available resources. The calculation process was performed using QM for Windows V5 software. The results showed that the optimal solution was to produce 1 Kg of Sagu Biscotti (X1) and 1 Kg of Brown Chips Sagu (X2), with a maximum profit value of  Rp. 75.000. These findings indicate that the Simplex method can generate optimal production combinations, maximize profit value, and improve resource allocation efficiency at Basyira Kukis MSME.